Gaya Hidup Mahasiswa: Sebuah Studi Mengenai Analisis Pengaruh Financial Knowledge Terhadap Sikap Hedonisme Di Kalangan Mahasiswa - Septiani, Fauzia; Hasanah, Aisyah Maliha; Azilla, Vika Hayatal; Muttaqin, Walady Ersa; Rozak, Rama Wijaya Abdul; Mulyani , Heni (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to see the relationship between financial literacy and financial knowledge on the style of hedonism among students. The method used is descriptive qualitative by distributing questionnaires via Google form to 100 students throughout Indonesia. The results showed that financial literacy and financial knowledge could affect financial management, while technology and the environment are supporting factors for the financial literacy process of students. Thus, hedonistic behavior is not always influenced by the student’s living environment; literacy and financial knowledge affect financial management more than technology and student living environment, which are the only supporting factors for student financial management.